Implementasi Kebijakan Alokasi Dana Desa (ADD) dalam Meningkatkan Pembangunan Desa (Studi Kasus di Desa Seletreng Kecamatan Kapongan Kabupaten Situbondo) - Nur Aidi Indana; Dwiyani Sudaryanti; Abdul Wahid Mahsuni (Universitas Islam Malang, 2023)
This study aims to find out how the Implementation of Village Fund Allocation Policies in Improving Village Development in Seletreng Village, Kapongan District, Situbondo Regency. The type of research is qualitative research. Interview and documentation techniques. The analytical method used is a qualitative analysis method. Based on the research results obtained by the researchers that the Implementation of the Village Fund Allocation Policy (ADD) in Seletreng Village, Kapongan District, Situbondo Regency is going well in increasing village development in accordance with the underlying regulations, but the role of the community in participating in village development is still lacking, so the authors conclude based on the results of information from informants and in accordance with empirical facts in the field, that the implementation of the Village Fund Allocation (ADD) program in Seletreng Village, Kapongan District, Situbondo Regency, namely Standards and policy targets/measures and policy objectives, human resources, characteristics of implementing organizations, attitudes of implementers, interorganizational communication and implementation, social environment, economics, and politics.Keywords: Implementation, allocation of village fund.